Overexpression of the Hsa21 Transcription Factor RUNX1 Modulates the Extracellular Matrix in Trisomy 21 Cells - Mollo, Nunzia; Aurilia, Miriam; Scognamiglio, Roberta; Zerillo, Lucrezia; Cicatiello, Rita; Bonfiglio, Ferdinando; Pagano, Pasqualina; Paladino, Simona; Conti, Anna; Nitsch, Lucio; Izzo, Antonella (Frontiers in Genetics, 2022)
Down syndrome is a neurodevelopmental disorder frequently characterized by other developmental defects, such as congenital heart disease. Analysis of gene expression profiles of hearts from trisomic fetuses have shown upregulation of extracellular matrix (ECM) genes. The aim of this work was to identify genes on chromosome 21 potentially responsible for the upregulation of ECM genes and to pinpoint any functional consequences of this upregulation. By gene set enrichment analysis of public data sets, we identified the transcription factor RUNX1, which maps to chromosome 21, as a possible candidate for regulation of ECM genes. We assessed that approximately 80% of ECM genes overexpressed in trisomic hearts have consensus sequences for RUNX1 in their promoters. We found that in human fetal fibroblasts with chromosome 21 trisomy there is increased expression of both RUNX1 and several ECM genes, whether located on chromosome 21 or not. SiRNA silencing of RUNX1 reduced the expression of 11 of the 14 ECM genes analyzed. In addition, collagen IV, an ECM protein secreted in high concentrations in the culture media of trisomic fibroblasts, was modulated by RUNX1 silencing. Attenuated expression of RUNX1 increased the migratory capacity of trisomic fibroblasts, which are characterized by a reduced migratory capacity compared to euploid controls.